2016
DOI: 10.32674/jis.v6i3.356
|View full text |Cite
|
Sign up to set email alerts
|

Examining Culture's Impact on the Learning Behaviors of International Students from Confucius Culture Studying in Western Online Learning Context

Abstract: There is a lack of shared understanding of how culture impacts learning in online environment. Utilizing document analysis, the authors in this research study culture’s impact on the learning behaviors of student sojourners from Confucius culture studying in Western online learning context. The shared understandings of Confucius culture and Western culture are compared, contrasted, and synthesized through Hofstede’s cultural dimensions theory. The learning behaviors of student sojourners from Confucius culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…They also said that when the students go to school, they are under the responsibility of their teacher. It supported by Kang & Chang (2016) who said that Eastern culture such as Taiwan, China Korea believe that teacher is more than just a lecturer because teacher has the moral role as a 'parent'. The Thailand students assume that their teacher is also their parents that they need to respect.…”
Section: Discussionmentioning
confidence: 99%
“…They also said that when the students go to school, they are under the responsibility of their teacher. It supported by Kang & Chang (2016) who said that Eastern culture such as Taiwan, China Korea believe that teacher is more than just a lecturer because teacher has the moral role as a 'parent'. The Thailand students assume that their teacher is also their parents that they need to respect.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the majority of college students taking online classes have experienced negative emotions, including anxiety and stress, during the COVID-19 pandemic (Fawaz & Samaha, 2021; Fitzgerald & Konrad, 2021; Gallego-Gómez et al, 2020; Masha’al et al, 2020). In particular, the reduced nonverbal communication and decreased peer/instructor interactions within online learning environments could amplify existing feelings of marginalization among ESL students or create a new sense of isolation for them (Kang & Chang, 2016). The current findings suggest that, to facilitate students’ academic success, nursing education programs must include interventions to decrease stressors related to remote learning and academic resources for all students—with a special focus on ESL students.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that ESL nursing students tend to show poorer academic performance in traditional face-to-face learning modalities and greater attrition rates, in addition to experiencing feelings of marginalization in their education than their native English-speaking counterparts (Eden et al, 2021; Englund, 2018; Lewis & Bell, 2020; Sailsman, 2021). Reduced nonverbal communication, a common characteristic in most e-learning courses (Arbour et al, 2015), could create additional challenges and amplify feelings of marginalization for ESL students from cultures and backgrounds where communication relies heavily on nonverbal cues (Kang & Chang, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, not all students respond the same way to pedagogies commonly used in Western educational systems. 1 International students experience different student learning practices. In east Asia, it's common for students to be accustomed to individual work, an all-authoritative teacher, ten-hour school days, and high-stakes exams.…”
Section: Library Instruction Practices and International Studentsmentioning
confidence: 99%